Diabetes mellitus manifestations and challenges in post-COVID-19 syndrome: A critical review - Sachin Shridhar Sakat, Vijaykumar Kuvar, Ajay Kharche, Milind Sagar, Prashant Kumar Pandey, Om Bagade, Rupali Bendgude, Ravindra Bendgude (Journal of Applied Pharmaceutical Science, 2024)
The human severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) has targeted millions of people globally leading to significant mortality in more than 3.5 million people. A spectrum of incapacitating symptoms or indications that may continue for a year and are consistent with COVID-19 emerge during or after an infection and cannot be explained by any other disorder. The term “long COVID” or “post COVID-19 syndrome (PCS)” refers to this collection of symptoms. While diabetes and COVID-19 have an antagonistic relationship, it is still not clear whether chronic hyperglycemia leads to an increased predisposition for PCS or whether people with PCS have a higher prevalence of newly diagnosed diabetes or prediabetes. A higher predisposition toward infectivity and mortality was recorded in persons with diabetes which made up about 35% of the patients who passed away from the illness. The SARS-CoV-2 infection and diabetes appear to be linked in three different ways. The infection is linked to a weakened immune system, ongoing inflammation, and maybe immediate pancreatic dysfunction. This review will explore the diabetes manifestations and associated challenges in COVID-19 and PCS. In addition, the review will also focus on the management strategies of diabetes with emphasis on the development of a comprehensive care plan for self-care among PCS patients.
Keywords: Post-COVID-19 syndrome, diabetes mellitus, inflammation, angiotensin-converting enzyme 2, pancreatic ß cells, diabetes management